The economics of health and wellness anthropological perspectives - Wood, Donald C. (Emerald, 2007)
This 26th volume in the Research in Economic Anthropology series differs in two main ways from all those that have come before. For one, it is the first REA volume to focus exclusively on the issue of health. In addition, it is not as concerned overall with economic or social theory, or with economic reasoning and action, as other volumes have been. Rather, it concentrates on the identification and analysis of important economic factors in the production of health and wellness. This volume consists of ten original anthropological papers that explore the general theme of the economics of health and wellness in a variety of ways. Some of these papers are more strongly ethnographic in nature, relying wholly on qualitative data derived from participant-observer methods at which ethnographers excel. Other papers successfully blend such information with quantitative data drawn from surveys, questionnaires, and even from biological samples.All papers, however, are grounded in empirical methods and based on data drawn from the personal investigations of the authors. Subjects and geographic areas represented in the volume are: Lakota residents of the Pine Ridge Indian Reservation in South Dakota, USA; rural people of Bangladesh; mental health care facilities and systems in Texas, USA; unsuccessful rural-urban migrants in Botswana, Southern Africa; loggers in British Columbia, Canada; municipal bus drivers in San Francisco, California; poor residents of Puebla, Mexico; slum dwellers of Lima, Peru; female victims of domestic abuse in Northern Vietnam; and, followers of Tibetan Buddhism in France. It features original articles written by experts in their fields. It is international in its scope.
Keywords: Health -- Social aspects.; Public health -- Cross-cultural studies.; Medical economics.; elektronické knihy; electronic books